Application of Project-Based Worksheets for Making Conditioner from Aloe Vera (Aloe vera L.) to Develop Students' Scientific Performance - Fatmala, Trie Rizqi; Windayani, Neneng; Irwansyah, Ferli Septi (Bumi Publikasi Nusantara, 2023)
This research aims to describe student activities, analyze student scientific performance at each learning stage, and analyze the characteristics of conditioners made from aloe vera (Aloe vera L.) by applying a project-based worksheet. The research method used was pre-experimental with a One-Shot Case Study design. The subjects of this research were students of class XI MIA MA Al-Jawami Cileunyi. The instruments used are learning descriptions, observation sheets, student worksheets (LKS), student scientific performance sheets and product assessment sheets. Data was obtained from observations of learning activities, filling out scientific performance sheets and product assessment sheets. The research results showed that overall student activity reached 94.8% with very good interpretation. The average value of student performance at all stages of learning by implementing project-based learning is 88.4 with good interpretation. The average value of students' scientific performance ability is 94.4 with very good interpretation. The average value of the characteristics of conditioners made from aloe vera as a whole is 98.4 with a very good interpretation. Thus, the application of project-based worksheets for making conditioner from aloe vera (Aloe vera L.) can develop students' scientific performance.